The influence of employee emotional intelligence on enterprise innovation performance using an adaptive mathematical modeling of emotions - Jie, H; Sanjuán Martínez, Óscar; González-Crespo, Rubén (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
Regular proportions of insight for emotional intelligence– for example, the IQ test – commonly center around the rationale and thinking in regions like math. Understanding cognizance has been considered a prominent research area in the present era. The possibility of this type of thinking supports the general achievement in the work environment, which is more powerful, and positively appears to be natural: It quantifies the person's capacity to get a handle on and orchestrate realities in their environment. In late years, the possibility that there is just a solitary type of knowledge that has gone under expanding the investigation. In this paper, the tests, learning about feelings, the capacity to perform assignments are identified with the information using an Adaptive Mathematical Modeling of Emotions (AMME) that has been designed mathematically. The fundamental contention is how the individual ought to act in a sincerely loaded circumstance, which does not pursue the individual who could do the detailed conduct adequately investigated in this research. © 2020 Elsevier Ltd
Keywords: computational model; emotional intelligence; feelings; Scopus